Reconstruction of Legal Protection for Nurses in the Provision of Hospital Nursing Care Based on Restorative Justice - Endro Haksara; Shohibul Hilmi; Elyani; Jaka Kusnanta; Henning Glaser (Nusantara: Journal of Law Studies, 2025)
Nurses play a central role in the delivery of healthcare services in hospitals, yet they remain vulnerable to legal risks arising from nursing practices, including allegations of malpractice and professional misconduct. Existing legal protections for nurses tend to emphasise punitive and procedural approaches, often neglecting principles of fairness, proportionality, and relational justice. This study aims to reconstruct the legal protection framework for nurses in the provision of hospital nursing care, grounded in the restorative justice approach. Employing a normative juridical research method, this study analyses statutory regulations, professional standards, court decisions, and relevant legal doctrines concerning nursing practice and health services. The findings reveal that current regulatory frameworks inadequately accommodate restorative mechanisms, resulting in legal uncertainty and psychological vulnerability for nurses during professional practice. This study proposes a restorative justice–based regulatory reconstruction that prioritises dialogue, accountability, victim recovery, and professional rehabilitation while maintaining patient safety and public trust. The reconstruction model emphasises mediation, proportional responsibility, and institutional support mechanisms as integral components of legal protection for nurses. This study contributes academically by offering a conceptual and normative framework for integrating restorative justice into nursing law and, practically, by providing policy recommendations for more humane, balanced, and sustainable legal protection in hospital nursing care.